Dane Rudhyar : His Music, Thought, and Art - Ertan, Deniz (Book collections on Project MUSE., 2009)
"Dane Rudhyar (1895-1985) was a unique figure in twentieth century American culture: a composer, thinker, painter, poet, novelist, and expert on astrology. His life and activities illuminate crucial twentieth-century American themes about society, history, creativity, and identity. Favoring synthesis and a blend of what he called unity and multiplicity, Rudhyar created a rare bridge between the West and the East, built on American foundations. His thought and work transcended disciplinary boundaries, integrating perspectives that were, and often still are, generally pursued in isolation from each other. The book is enriched with numerous color illustrations of Rudhyar's paintings and with examples drawn from his music and writings."--Jacket.